Análise, desenvolvimento e projeto de um conversor duplo Forward on-off zcs para aplicação em fontes chaveadas isoladas - Andrade, Alexandre Motta de (2012)
A complete study of a topology resulting from a combination of two Forward structures, attached to the same magnetic core of a transformer and operating as a Full-Bridge converter is presented. In order to reduce the switching losses and the electromagnetic interference, a soft commutation cell that provides ZCS commutation of all the switches is implemented. This converter limits the current on the main switches at the load current because diverts the sinusoidal half cycle to a auxiliary switch. This way, a new Double Forward On-Off ZCS was developed.